Effect of Pistacia vera on Listeria monocytogenes and protein extraction by electrophoresis - Elham Al Khashab; Ekbal Sultan; Ameera Hamdoun (College of Education for Pure Sciences, 2010)
ABSTRACT Listeria monocytogenes was isolated from 50 samples of minced red meat, which was collected randomly from Mosul city then it was diagnosed using selective media and biochemical test, the inhibitory ackivity of extracts of seeds of pistacia vera which was protein. oil and steroid test of this extracts was done on Listeria monocytogenes and compared with bacterial standard antibioties. The Proteinous extract of Pistacia vera showed a high inhibitory effect on Listeria monocytogenes compared with oil and steroids extracts. Eleotrophorosis was used in order to separate the Protein of Porteinous extracts, the molecular weight of these Proteins were determined. (20) ,(48), (54), (63), (130). Killodaltone, respectivly.